Job Insecurity, Financial Threat, and Mental Health in the COVID-19 Context: The Moderating Role of the Support Network. (September 2022) - Alcover, Carlos-María; Salgado, Sergio; Nazar, Gabriela; Ramírez-Vielma, Raúl; González-Suhr, Carolina
The aim of this study is two-fold. Firstly, to analyze the relations between the perceptions of job insecurity and financial threat and general mental health during the early stage of the COVID-19 pandemic. And secondly, to identify the potential moderating effect of the support network. We carried out a cross-sectional study on a non-probabilistic sample aimed at a general Chilean adult population to analyze this. The results show that both job insecurity ( β  = −.183; p  < .001) and financial threat ( β  = −.309; p  < .001) are associated with a decline in general mental health. Likewise, the results indicated a positive relationship between support network and general mental health in the two models analyzed ( β s = 0.322 and 0.182; p s < 0.001 and = 0.012, respectively), as well as a moderating effect of support network on the relationship between job insecurity and decreased general mental health ( β  = .232; p  < .001). The theoretical and applied scope of these findings are analyzed, and their challenges and limitations are discussed.